IDENTIFICATION OF REPRODUCTIVE PERFORMANCE OF BALI COWS (Bos sondaicus) ARTIFICIAL INSEMINATION ACCEPTORS IN ORDER TO SUPPORT THE UPSUS SIWAB PROGRAM IN BADUNG AND TABANAN REGENCIES - I G., Suranjaya; Sarini, N. P.; Anton, A.; Wiyana, A. (Majalah Ilmiah Peternakan; Vol 22 No 2 (2019): Vol. 22 No.2 (2019)DO - 10.24843/MIP.2019.v22.i02.p06, 2019)
This research was conducted in Badung and Tabanan Regencies with a survey method on bali cow farmer group where the cows as artificial insemintion (AI) acceptors were in the the program of special effort on acceleration of pregnant cattle and buffalo population (Upsus Siwab). Sampling was carried out by purposive random sampling with 74 cows were in Badung and 61 cows were in Tabanan. Data obtained from interviews and recording from farmers, farmer groups and inseminator staffs. Data collected included: age of cows, age of first mated, calving rate, service per conception, gestation period, and post partus heat. Data generated were analysed using descriptive statistics and reproductive performance of bali cows as AI acceptors between Badung Regency and Tabanan Regency was analysed using Two Independent Sample T Test. Results showed that the average age of cows in Badung and Tabanan was 4.23 ± 2.00 years and 4.50 ± 2.90 years and the age at first mated was 1.74 ± 0.49 and 1.900.38 years respectively. Calving rate of cows as AI acceptors in Badung and Tabanan Regencies were 56.75% and 40.98% respectively. Service per conception is 1.62 ± 0.39 times and 1.90 ± 0.38 times, respectively. The average of gestation period of cows in Badung 9.63 ± 0.52 months tended to be longer than of 9.45 ± 0.22 months in Tabanan, whereas the post partus heat were 3.06 ± 0.94 months and 3.53 ± 1.03 months, respectively. In conclusion, the calving rate of cows in Badung was greater than of in Tabanan and the post partus heat of AI acceptor cows in Badung was shorter than of in Tabanan.